EVALUASI BLOK SENDI FASET LUMBAL PADA NYERI PUNGGUNG BAWAH KRONIK AKIBAT KELAINAN SENDI FASET - Dessy Rakhmawati Emril,* Devi Inkha,* Endang Mutiawati,* Nova Dian Lestari,* Thomas Eko Purwata** (Neurona Majalah Kedokteran Neuro Sains, 2016)
INTRODUCTION CHRONIC LOW BACK PAIN LBP REMAINS THE IMMENSE PROBLEM FACED BY DOCTORS NOWADAYS LUMBAR FACET JOINT HAS BEEN SHOWN AS THE SOURCE OF CHRONIC PAIN IN 21 TO 41 OF LOW BACK PAIN PATIENTS